Assessment on 5S Approach Strategy for Small Medium Enterprise (SME): A Case Study in Sabah - Radzali, Mohd Adzrie; Vincent Thomas, (Journal of Advanced Mechanical Engineering Applications, 2020)
This study aims to assess the 5S approach strategy for SME. 5S in simple terms is a Japanese technique consisting of five ‘S’ terms namely Seiri (sorting), Seiton (set in order), Seiso (shine), Seiketsu (standardize) and Shitsuke (sustain) which is always applied to manage the workplace. The aim of 5S in the organization is to organize a work space for efficiency and effectiveness by identifying and storing the items used, maintaining the area and items, and sustaining the new order. To achieve the project objectives, a case study will be steered at packaging section of Fatt Choi Sdn Bhd Company located in Sabah, Malaysia to gather data for analysis. The level of understanding for workers to encounter and adapting 5S systems which would enhance their performance was being assessed. Apart from that, this study also evaluated the acceptance rate for employees to implement 5S in their work area as well as to relate the effectiveness of the 5S system in improving the worker performance and reducing unwanted waste in the industry. Besides that, the problem faced during the implementation of 5S, factors that affect the implementation and benefits experienced after the adoption of 5S lean manufacturing tools were being identified and evaluated.